Text as a Symbol. Towards a Hermeneutics of Recognition - Munteanu, Cristinel (Acta Universitatis Danubius. Communicatio, 2022)
In this article I will try to provide some elements for establishing a sui generis hermeneutics, that is a “hermeneutics of recognition”, referring to certain texts considered as symbols. In order to do this, I need to restore the etymological meaning of the term symbol (< O.Gr. symbolon), analysing, first of all, the word as a symbol, as it was defined by Aristotle. In this regard, I will appeal to important thinkers such as Eugenio Coseriu, Hans-Georg Gadamer, José Ortega y Gasset and others. Leaving apart the classic types of texts which were recorded by Liddell & Scott’s Lexicon as symbola (e.g. political or commercial treaties), I will also mention the Christian Credo and I will particularly discuss the famous exchange of letters between Alexander the Great and Aristotle.